Survei Alat Kursi Roda Inovasi Terhadap Hasil Lemparan - Gempar Al-Hadist; Arif Fajar Prasetiyo (LPPM Politeknik Pratama, 2023)
Persons with disabilities are everyone who has physical and/or mental disorders that can interfere or constitute obstacles and obstacles for him to carry out activities properly. The condition in which a person is physically or mentally imperfect is often referred to as disabled or persons with disabilities. The objectives of preparing Assistive Technology for Students with Special Needs are: Encouraging the University of Subang to expand access to education for individuals with special needs. The benefit of this program is to help students with special needs in carrying out the learning process, as well as assisting lecturers in providing lecture services to students with special needs during the learning process. Other resources/parties involved are students, lecturers, quality assurance institutions (LPM), athletes with disabilities who are members of the Subang Regency NPCI. This wheelchair assistive technology was developed using the 4D method (define, design, develop, and disseminate).